Gender Imbalances among Students in Kyambogo University of Uganda and Development Implications - Lubaale, Grace (Online Submission, 2020)
Kyambogo University (KyU) is one of the nine government universities in Uganda experiencing gender inequalities with glaring development implications in the country with 34.6 million people (UBOS, 2016) in which women are the majority. The central aim of the paper is to establish the gender imbalances in Kyambogo University and development implications with a specific focus on policies, facilities, and services for students and then provide the way forward. This study used a mixed-methods approach that combined desk reviews and interviews (Creswell et al., 2017). The findings indicate that nature is reflected in the admissions, completion, science and engineering programmes and student leadership while the development implications are colossal in terms of imbalances in Kyambogo University dropouts, Student Leadership, Higher Degree Achievements, returns to education, and lose of Self-Esteem. In conclusion, it is now clear that gender imbalances in KyU is a reality and this paper recommends promoting gender equality by all stakeholders majorly through the KyU Gender Mainstreaming Directorate, and through the establishment and operationalization of KyU Gender Policy, Anti-Gender Violence Policy, Gender Responsive Budgeting, STEM Programme, and Gender Monitoring and Evaluation.